Poisonous Substances in Cigarette Tobacco - Abd Razak, Dzulkifli (1995)
Cigarettes contain thousands of poisonous substances. Therefore, it is imperative that attempts be made to end unnecessary exposures to cigarette smoke, and prevent unnecessary exposure to cigarette smoke to prevent suffering. The situation is even more dangerous in the case of Environmental Tobacco Smoke (ETS) which contributes significantly to 'passive smoking. (see, Megazine, April 13, 1995). This is because the amount of chemicals/poisons found in ETS can range from twice to 50 times as much, compared with normal (mainstream) cigarette smoke. Some of these are as follows: Nicotine:It has twice the amount of ETS relative to "mainstream" smoke. 2 times Tar:It has two to five times the amount of ETS relaive to "mainstream" smoke. Carbon monoxide:It has five times the amount of ETS relative to "mainstream" smoke. Hydrogen cyanide:It has four to six times more ETS relative to "mainstream" smoke. Toluene:It has six to eight times more ETS relative to "mainstream" smoke. Nitrosamine (carcinogen): It has 50 times the amount of ETS relative to "mainstream" smoke.